Communal Effect Attitudes on Punjab Senior Citizens - Kaur, Navjot; Parihar, Priyanka (International Review of Management and Marketing, 2024)
Among the most vulnerable groups in society is the elderly, who face issues such as a deteriorating feeling of self-worth brought on by physical weakness, a dwindling social position, and limited financial resources. Feelings of insignificance have been exacerbated by the fact that families are finding it more difficult to care for the elderly due to socioeconomic and demographic changes. As a result, psychological difficulties frequently outweigh outward indications of aging as people age. With a specific focus on 260 senior individuals in Punjab between the ages of 60 and 90, this study sought to investigate the effects of family and social attitudes toward the old. The majority of respondents claimed financial independence, but only 11% reported having stable finances due to rental income and savings account interest. But 8% struggled to pay for everyday needs, and some experienced severe financial difficulties related to fundamental needs and family responsibilities. Remarkably, only 11.7% of older people consistently created strong social relationships, compared to 76.6% who did so on occasion. Furthermore, 16.7% of respondents admitted to their situation, suggesting a greater dedication to maintaining family togetherness. The behavioral changes aligned with the perceptions of 83% of senior respondents who observed a shift in the way older persons view their basic obligations. Family dynamics, economic dependence, physical abuse cases, feelings of isolation, inadequate social support, family members' disdain, and food-related issues were among the main concerns. The study emphasized the complex relationships that exist between aging, health problems, decreased physical activity, and elder abuse. It also clarified the critical roles that qualities, social interactions, financial dependence, and behaviors have in influencing these relationships.